PENGARUH PENGGUNAAN MEDIA PEMBELAJARAN BERBASIS WORDWALL TERHADAP MINAT BELAJAR SISWA PADA PEMBELAJARAN IPS SEKOLAH DASAR - Veni Veronika; Rury Rizhardi; Ida Suryani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine whether there is an influence of using Wordwall-based learning media on students' learning interests in elementary school social studies. This type of quantitative research uses experimental methods with a true experimental design and a posttest-only control design. This research was conducted at SD Negeri 1 Bakam and carried out in class V with a total of 49 students. The results of this research show that the average score obtained by the researcher from the experimental class posttest questions was 88.8, while the control class was 76. Based on data analysis using the Independent Samples Test with the Ha criterion, it was accepted if tcount > ttable with tcount = 9.023 and ttable = 1.67793 with a significance level of 0.05, so Ha is accepted. Based on the research results, it can be concluded that there is an influence of using wordwall-based learning media on students' learning interests in elementary school social studies.